Desempenho de escolares em provas de processo de identificação de letras e do processo léxico - Oliveira, Adriana Marques De; Germano, Giseli Donadon; Capellini, Simone Aparecida (ABRAMO Associação Brasileira de Motricidade Orofacial, 2016)
ABSTRACTPurpose: to describe, compare and correlate the performance of Brazilian students from 2nd to 5th grade of Elementary Schools in public and private institutions for tests of letter identification and lexical process evaluation.Methods: 262 students attending Elementary Schools (122 from public school and 140 from private school), in the interior of São Paulo State: Public School - G1 (2nd grade, n=24); G2 (3rd grade, n=33); G3 (4th grade, n=31); G4 (5th grade, n=34) and Private School - G5 (2nd grade, n=37); G6 (3rd grade, n=34); G7 (4th grade, n=34); G8 (5th grade, n=35. Tests of Letter Identification and the Lexical process from PROLEC were applied.Results: the students from private school showed superior average performance, except for the same-different test between G1-G5 and G3-G7 groups. The differences were higher among the students up to de 4th grade, due to the frequent use of the phonological route. This suggests differences in teaching the Portuguese alphabetic principles in in private and public schools. For the 5th grade there was no evidence of difference for tests in which words could be read by the lexical route.Conclusion: the students from private school showed superior performance, except for the tests in which the phonological route was not entirely required. However, in the beginning of literacy, the phonological route was more used than the lexical route, regardless of the type of school. This study shows the education system necessity for prioritizing in early literacy the letter-sound relationship, so the students from public institutions can present better decoding results, which can directly impact reading and comprehension.

RESUMOObjetivo: caracterizar, comparar e correlacionar o desempenho de escolares brasileiros do 2º ao 5º ano do Ensino Fundamental do ensino público e particular em provas de avaliação do processo de identificação de letras e do processo léxico.Métodos: participaram 262 escolares do Ensino Fundamental (público= 122, particular= 140), do interior paulista: Ensino público - G1 (2º ano, n=24); G2 (3º ano, n=33); G3 (4º ano, n= 31); G4 (5º ano, n=34) e Ensino particular - G5 (2º ano, n=37); G6 (3º ano, n=34); G7 (4º ano, n=34); G8 (5º ano, n=35). Aplicadas Provas do processo de Identificação de Letras e Léxico do PROLEC.Resultados: os escolares do ensino particular apresentaram desempenho médio superior, com exceção da prova Igual-Diferente entre os grupos G1-G5 e G3-G7. As diferenças foram maiores entre os escolares até o 4º ano devido ao uso frequente da rota fonológica, sugerindo diferença no ensino do princípio alfabético entre as escolas públicas e particulares. Para o 5º ano, não houve diferença nas provas em que as palavras podem ser lidas pela rota lexical.Conclusão: os escolares do ensino particular apresentaram desempenho superior, com exceção das provas em que a rota fonológica não é a unicamente exigida. Contudo, no início da alfabetização, a rota fonológica foi mais utilizada do que a lexical, independente do tipo de ensino. Este estudo mostra a necessidade de o sistema de ensino priorizar na alfabetização a relação letra-som, de modo que os escolares de escola pública possam apresentar melhores resultados em decodificação que podem influenciar diretamente a compreensão e leitura.
Students' performance in letter identification and lexical process tests
Keywords: Reading; Evaluation; Learning; Education, Primary and Secondary; Leitura; Avaliação; Aprendizagem; Ensino Fundamental e Médio